The Effectiveness of ESA Method towards Students' Vocabulary Mastery - Nggolaon, Desriani; Ita Rosvita; Fegi Astrianti (English Education Study Program, 2024)
This research aims at knowing whether the use of ESA is effective to increase the students' vocabulary mastery of the eighth grade at MTSN 1 Banggai or not. The research design of this study was quantitative research design with using quasi-experimental research. The population of this research was the eighth grade students of MTSN 1 Banggai. The research sample was chosen by using purposive sampling; class VIII A as the experimental class and class VIII B as the control class. Each class consist of 35 students. Test was used as the main instrument to collect data. The test was given twice in pretest and post-test. The results show that: 1) the mean score from pretest 52,34 in experimental class was significantly increased into 74,48 in post-test. While in control class, there were also an improvement but not as significant as in experimental class. The mean score of pretest 50,65 in control class was only increased in post-test become 57,60. 2) by applying signicance level 0,05 with degrees of freedom 68, the t-counted was 10,16 was greater than the t-table 1,66. The alternative hypothesis (Ha) of this study is accepted while the null hyphotesis (Ho) is rejected. It means that the ESA method is effective to increase students’ vocabulary mastery of Class VIII A at MTS Negeri 1 Banggai.